CRABS CLAW and SUPERMAN Coordinate Hormone-, Stress-, and Metabolic-Related Gene Expression During Arabidopsis Stamen Development - Lee, Ze Hong; Tatsumi, Yoshitaka; Ichihashi, Yasunori; Suzuki, Takamasa; Shibata, Arisa; Shirasu, Ken; Yamaguchi, Nobutoshi; Ito, Toshiro (Frontiers in Ecology and Evolution, 2019)
The appropriate timing of the termination of floral meristem activity (FM determinacy) determines the number of floral organs. In Arabidopsis, two transcription factors, CRABS CRAW (CRC) and SUPERMAN (SUP), play key roles in FM determinacy. CRC belongs to the YABBY transcription factor family, whose members contain a zinc finger and a helix-loop-helix domain. The crc mutation causes the formation of unfused carpels and leads to an increase in carpel number in sensitized backgrounds. The SUP gene encodes a C2H2-type zinc-finger protein, and sup mutants produce extra carpels and stamens. However, the genetic interaction between CRC and SUP is not fully understood. Here, we show that these two transcription factors regulate multiple common downstream genes during stamen development. The crc sup double mutant had significantly more stamens and carpels than the parental lines and an enlarged floral meristem. Transcriptome data have implicated several cytokinin- and auxin-related genes as well as stress- and metabolic-related genes to function downstream of CRC and SUP during stamen development. The regulation of common downstream genes of CRC and SUP might contribute to the initiation of an appropriate number of stamens and to subsequent growth and development.